Differentiated Learning as an Effort to Improve Students Learning Outcomes in Physics Subjects - Dewi Fajaryati; Haratua Tiur Maria S; Venny Karolina (IJESS International Journal of Education and Social Science, 2023)
Differentiated learning refers to a learning approach where teachers can adjust teaching methods to take into account individual differences in the class. Differentiated learning has become the main focus in today's flexible learning and assessment processes, both for teachers and students in the classroom. This research was conducted with the aim of exploring the implementation of differentiated learning and digging more deeply into its impact on student learning outcomes at SMA Negeri 1 Selakau in Physics subjects. The results obtained were an average pre-test value of 43.14 and an average post-test value of 76.71 with a sig level. 0.000 through the Paired Samples T-test so that there is a significant difference in the pre-test and post-test results in differentiated learning in physics subjects in class XF with a sample population of 35 people showing an increase of 33.57. Therefore, this differentiated learning is highly recommended to be implemented by teachers at the Senior Secondary School level in all subjects so that student learning outcomes can improve because it is well facilitated according to each individual's unique character.